Menanamkan Jiwa Kewirausahaan melalui Sosialisasi Kewirausahaan dan Lomba Kreativitas Wirausaha tingkat SD/MI di Desa Pakel - Ilham Fitri Nurilhuda; Sumainah Fauziah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Pakel Village has many MSMEs, therefore, entrepreneurship socialization and creativity competitions were held to instill an entrepreneurial spirit in children in Pakel Village. On Saturday, May 27, 2023, the committee started the activity with entrepreneurship socialization which was presented using a laptop and PowerPoint slides which were displayed using a projector. The committee also used questions and answers to provide opportunities to ask questions to participants, gave questions with prizes to participants, and held an ice-breaking session in the middle of the event to make the atmosphere not tense. Next, the competition was held and participants had 90 minutes to make crafts, and continued at home until May 30, 2023. On Tuesday, May 30, 2023, participants gathered at the village hall to present their work. The jury gave a curation consisting of selling value, ideas, language style and facial expressions, as well as the beauty and neatness of the decoration. The prizes given were goodie bags, pins, trophies, medals, and competition certificates. The results of the activity provided an entrepreneurial spirit and insight related to entrepreneurship for SD/MI children in Pakel Village. This activity is expected to provide a bright future for SD/MI children in Pakel Village.